Answer:
the center is at (1, -3)
Explanation:
The center-radius form of the circle equation is in the format (x – h)2 + (y – k)2 = r2, with the center being at the point (h, k) and the radius being "r".
So we need to write the ecuation x^2 + y^2 - 2x + 6y + 9 = 0 in the format above.
So we have:
x^2 + y^2 - 2x + 6y + 9 = (x^2 -2x + 1) + (y^2 + 6y + 9) - 1
(x^2 -2x + 1) + (y^2 + 6y + 9) - 1 = (x-1)^2 + (y+3)^2 - 1
So now, looking at the equation: (x-1)^2 + (y+3)^2 = 1
We know that h=1 and k=-3. So the center is at (1, -3)